Correlations between Emotional Intelligence with Achieved Cumulative Grade Point Average (GPA) of Undergraduate Students of Faculty of Medicine, Sebelas Maret University - Witjaksana, Risnu Ardian; Subandono, Jarot; Murti, Bhisma (Nexus Pendidikan Kedokteran dan Kesehatan, 2016)
Introduction: Healthcare service could not be distinguished from medical education in Indonesia. Beside his academic capabilities, a doctors behaviour towards his surroundings must also be taken into account. But in reality, there hasnt been a significant amount of emotional intelligence teaching included in the curriculum of Indonesian medical education. This study is conducted to define the Correlations between Emotional Intelligence with Achieved Cumulative Grade Point Average (GPA) of Undergraduate Students of Faculty of Medicine, Sebelas Maret University Surakarta. Method: This study was an analytic observational experiment with cross sectional approach. The sample had been taken from the population of undergraduate students of Faculty of Medicine, Sebelas Maret University, class of 2012. The sampling had been done using cluster random sampling technique. The obtained data had been statistically analyzed with simple linear regression technique, using Statistical Package for Social Sciences23 (SPSS 23) for Mac and p <0.05 was chosen as the minimal significance level. Result: The data analysis result with simple linear regression technique showed that there was no significant correlation between emotional intelligence and the achieved cumulative grade point average (GPA) in undergraduate students of Faculty of Medicine, Sebelas Maret University Surakarta. (p = 0.536 ; p>0.05). Conclusion: There was no significant correlation between emotional intelligence and the achieved cumulative grade point average (GPA) in undergraduate students of Faculty of Medicine, Sebelas Maret University Surakarta. Keywords: emotional intelligence, cumulative grade point average (GPA), undergraduate students of faculty of medicine.